2005
DOI: 10.1255/ejms.729
|View full text |Cite
|
Sign up to set email alerts
|

Letter: Multiply Charged Ions in Matrix-Assisted Laser Desorption/Ionization Generated from Electrosprayed Sample Layers

Abstract: Ultraviolet matrix-assisted laser desorption/ionization (UV-MALDI) detection of ions with charge states as high as those usually seen with electrospray ionization (ESI), was recently demonstrated by Gologan, Cooks and co-workers in soft-landing experiments. 1 In theses experiments, multiply charged ions of proteins generated by ESI were landed in high vacuum (~10 -8 torr) onto self-assembled monolayer (SAM) surfaces. To analyze the deposited protein material, laser desorption mass spectrometry (LD-MS) was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…Previous research on the charge distribution focused on the opposite, namely the search for parameters to increase the number of multiply charged cations since higher charge states open the way to extend the accessible mass range of instruments with limited m/z range and enhance the fragmentation for structural investigations. Elevated gas pressure in the source region [12,13] laser powers just above the threshold [12], addition of glycerol [14], electrospray-deposition onto a matrix layer [15], low abundance of photoelectrons by thick sample layers or deposition on an "electron-free" surface [16][17][18], and matrices with low proton affinity (such as alphacyano-4-hydroxycinnamic acid (CHCA)) [19], favor the presence of higher charge states for polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the charge distribution focused on the opposite, namely the search for parameters to increase the number of multiply charged cations since higher charge states open the way to extend the accessible mass range of instruments with limited m/z range and enhance the fragmentation for structural investigations. Elevated gas pressure in the source region [12,13] laser powers just above the threshold [12], addition of glycerol [14], electrospray-deposition onto a matrix layer [15], low abundance of photoelectrons by thick sample layers or deposition on an "electron-free" surface [16][17][18], and matrices with low proton affinity (such as alphacyano-4-hydroxycinnamic acid (CHCA)) [19], favor the presence of higher charge states for polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Demirev et al have demonstrated the utility of this approach in profiling bacterial proteomes [32]. A key factor in expanding the useable mass range will be the ability to generate multiply charged ions from MALDI ion sources: therefore, examination of MALDI sample preparation strategies, such as non-metallic surfaces [28] and electrospray deposition [31] or even the recently reported MALDESI approach [44], is an important area of future investigation. Obviously, the analytical parameter space available for exploration is large, including sample preparation, activation methods, hardware/software improvements; however, the utility of the approach has been demonstrated albeit with a limited number of small proteins.…”
Section: Discussionmentioning
confidence: 99%
“…When the matrix/ analyte is co-crystallized on polyether ether ketone, an "electron free" surface, an unusually large fraction of multiply charged ions is produced, compared with the normally used stainless steel surface [28]. The charge state, as well as the signal intensity, is also related to the way the sample is spotted as evidenced by electrospray deposition of analyte resulting in multiply charged ions being produced at threshold laser irradiance [31]. There is one report of the use of multiply charged precursor ions in MALDI TOF-TOF experiments for protein identification in bacterial proteomes [32] that demonstrates the advantage of using multiple precursors to enhance database searching results.…”
mentioning
confidence: 99%
“…One of these employed electrospray deposition of at least 200 pmol of analyte on various preformed MALDI matrix layers, showing that under specific conditions highly charged insulin ions can be detected albeit at a low signal-to-noise ratio. [15] Herein, we report progress in achieving high and prolonged yields of multiply charged peptide and protein ions using liquid UV-MALDI matrices and an AP ion source with an ion transfer tube that can be used at variable elevated temperatures of up to 400 8C. The liquid matrices described herein are based on 2,5-dihydroxybenzoic acid (DHB) or acyano-4-hydroxycinnamic acid (CHCA) with the addition of glycerol and triethylamine in various concentrations.…”
mentioning
confidence: 99%